PEDAGOGICAL EXPERIMENT OF THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE MANAGERS OF PHYSICAL CULTURE AND SPORTS, INFORMATION AND COGNITIVE CRITERIA IN INSTITUTIONS OF HIGHER EDUCATION - Kryshtanovych, Svitlana (Mountain School of Ukrainian Carpaty, 2020)
The article defines the basis of experimental research and establishes the methodology of the experiment, which included the purpose, objectives, selection of variable components, justification of measuring instruments, description of the experimental procedure and generalization of the experimental results. To solve the problems at different stages of experimental research, research methods and techniques were used, including mathematical statistics for quantitative and qualitative analysis and verification of experimental research results: method of estimating the reliability of averages, method of measuring and mathematical data processing; Student's t-test - to determine the presence or absence of statistical discrepancy between the two means, which are given in absolute values. For the reliability of the pedagogical experiment, undergraduates in the field of knowledge 017 «Physical Culture and Sports» were involved in 5 institutions of higher education in Ukraine. The control group and the experimental group were separated.To divide the groups into experimental and control, their academic success was analyzed by disciplines that are fundamental for the formation of professional competence of future managers of physical culture and sports on the information and cognitive criteria. It is established that the indicators of the information-cognitive criterion are the system of knowledge of professional disciplines on professional training and the ability to use research skills. The results of a pedagogical experiment to determine the formation of professional competence of future managers of physical culture and sports according to the information-cognitive criterion are analyzed. During the study it was found that the result of the formative stage of the pedagogical experiment is to increase the level of professional competence of managers of physical culture and sports in masters on information and cognitive criteria, which will contribute to their future management.